Inflation and Economic Growth: An Empirical Evidence of Bangladesh (1986-2016) - Sumon, Khairul Kabir; Miyan, Md. Sazib (International Journal of Economics and Financial Issues, 2017)
The study is conducted to examine empirically the relationship between inflation and economic growth in Bangladesh using annual data set from 1986 to 2016. Moreover to formulate policy issue, it was needed to find the threshold level of inflation for Bangladesh. Based on the results of two steps Engle-Granger and Johansen Co-integration test, it confirms that there is statistically significant positive relationship between inflation and economic growth. The results of the error correction model, specifically the sign of the one period lagged error correction term confirm that inflation adjust itself to long-run path approximately at the speed of 79% in each year. Finally based on the Conditional Least Square (CLS) method the forecasted threshold level of inflation is 8%; any rate beyond this, does not significantly influence the growth rate. Keywords: Economic growth, Inflation, Threshold level of inflation, Co-integration, ECM, CLS JEL Classifications: C13, C32, C51, C52, E31, O42